Blood pressure-lowering effect of dietary (-)-epicatechin administration in L-NAME-treated rats is associated with restored nitric oxide levels - Litterio, Maria Corina (2012)
Epidemiological and intervention studies have shown that the intake of certain chocolates or cocoa products decreases blood pressure (BP) in humans. (-)-Epicatechin is the most abundant flavanol present in cocoa seeds and its derived foods. This work investigates the effects of dietary (-)-epicatechin on BP in rats that received Nω-nitro-l-arginine methyl ester (L-NAME) for 4 days. (-)-Epicatechin administration prevented the 42 mm Hg increase in BP associated with the inhibition of NO production in a dose-dependent manner (0.2-4.0 g/kg diet). This BP effect was associated with a reduction in L-NAME-mediated increase in the indexes of oxidative stress (plasma TBARS and GSSG/GSH2 ratio) and with a restoration of the NO concentration. At the vascular level, none of the treatments modified NOS expression, but (-)-epicatechin administration avoided the L-NAME-mediated decrease in eNOS activity and increase in both superoxide anion production and NOX subunit p47phox expression. In summary, (-)-epicatechin was able to prevent the increase in BP and in oxidative stress and restored NO bioavailability. The fact that (-)-epicatechin is present in several plants usually consumed by humans gives the possibility of developing diets rich in those plants or pharmacological strategies using that flavonoid to diminish BP in hypertensive subjects.